Distributed Routing Protocol which increasing Quality of Service for Hybrid Wireless Network - Thakur, Uma k; Dethe, CG (International Journal of Computer Sciences and Engineering, 2025)
Wireless transmission is the reserch field for the researcher for increasing the quality of service. With the expanding level of wireless transmission in today's condition, individuals regularly required QOS for sharing their information between the hubs. For bearing QOS to the client, numerous specialists proposed a lot many techniques to give QOS ensured directing to hybrid systems, they endeavor to enhance the system limit and dependability yet they avoid oblige in QOS. For this issue, our principle goal of this paper is to enhance the QOS and proficiency of directing methodology with compels over hybrid wireless data spilling utilizing QOD convention. This expects to build up the QOS based reliable architecture against the hybrid wireless routing issues. The framework likewise goes for giving both proactive and responsive answers for powerful routing. The objective of this paper is to give a proficient element routing management to bargain with difficulties of information transmission to channel the neighbor hubs through which the next hop transmission happens.